A whole lot of Wayne - McRobbie, David; McRobbie, David; McRobbie, David; McRobbie, David (Crows Nest, NSW, Australia : Allen & Unwin, 2007)
Contains twenty-five stories featuring a boy named Wayne and his friends Squocka, Fat Cat, and Violet Pridmore, and details his adventures, his grand imagination, and his encounters with a bully named Kevin Merry.
"This collection has been adapted from stories in The Wayne dynasty, Waxing with Wayne and A little drop of Wayne published by Mammoth Australia in 1989, 1991 and 1994"--T.p. verso.
School Library Journal
4.6
3-6.
3-6
Keywords: Bullying -- Juvenile fiction; Friendship -- Juvenile fiction; Imagination -- Juvenile fiction; Bullies -- Fiction; Friendship -- Fiction; Imagination -- Fiction; Bullies -- Fiction; Friendship -- Fiction; Imagination -- Fiction